1999
DOI: 10.1128/mcb.19.6.4093
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Group II Introns, Cytochrome c Oxidase, and Senescence in Podospora anserina

Abstract: Podospora anserina is a filamentous fungus with a limited life span. It expresses a degenerative syndrome called senescence, which is always associated with the accumulation of circular molecules (senDNAs) containing specific regions of the mitochondrial chromosome. A mobile group II intron (alpha) has been thought to play a prominent role in this syndrome. Intron alpha is the first intron of the cytochrome c oxidase subunit I gene (COX1). Mitochondrial mutants that escape the senescence process are missing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…It was previously reported that when intron RNA circles are found, intron DNA circles or at least head-to-tail intron DNA junctions could also be detected (Osiewacz and Esser 1984;Schmidt et al 1994;Begel et al 1999;Murray et al 2001;Molina-Sánchez et al 2006;Federova and Zingler 2007). However, the origin, the nature, and the significance of these head-to-tail intron DNA junctions are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that when intron RNA circles are found, intron DNA circles or at least head-to-tail intron DNA junctions could also be detected (Osiewacz and Esser 1984;Schmidt et al 1994;Begel et al 1999;Murray et al 2001;Molina-Sánchez et al 2006;Federova and Zingler 2007). However, the origin, the nature, and the significance of these head-to-tail intron DNA junctions are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Intron RNA circles were previously observed in vitro (Murray et al 2001;Nagy et al 2013) and in vivo (Li-Pook-Than and Bonen 2006;Molina-Sánchez et al 2006Dalby and Bonen 2013) but the circularization pathway was not addressed. Interestingly, the presence of intron RNA circles in vivo can be accompanied by traces of head-to-tail intron DNA junctions (Osiewacz and Esser 1984;Schmidt et al 1994;Begel et al 1999;Murray et al 2001;Molina-Sánchez et al 2006;Federova and Zingler 2007). The nature, the origin and the function of these intron DNA junctions where the 5 ′ and 3 ′ end of the intron are precisely joined is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Implants were removed at approximately 1 cm from the margin of dead mycelia. The specific probes used to reveal senDNA␣ and -␥ have been described previously (5). Total RNA was extracted according to the method of Lecellier and Silar (28) for 5Ј rapid amplification of cDNA ends (RACE) or by the guanidinium thiocyanate-phenol-chloroform method (20) for cDNA preparation and Northern blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting vector, pPableDPaAnt Mitochondrial DNA analysis: The mtDNA of the different growing or dying cultures was extracted by minipreparation (Lecellier and Silar 1994). The probes used in this study were EcoIV, EcoI, and 2604 ( described previously by Begel et al 1999); they cover $80% of the mitochondrial genome.…”
mentioning
confidence: 99%